Pengembangan Budaya Pesantren Berbasis Kearifan Lokal di Pondok Pesantren Putri Salafiyah Bangil dan Pondok Pesantren Ali Ba’alawi Kencong Jember - Syarifatul Marwiyah (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
The objective of this study is to examine the development islamic boarding school of culture based on local wisdom in islamic boarding school Salafiyah Bangil and Islamic boarding school Ali Ba’alawi Kencong Jember. This study is qualitative research with a transcendental phenomenological approach with a multi-site design. The techniques of data collection by using in-depth interviews, observation, and documentation. The data were analyzed in two steps, they are by analysing the single site data analysis and cross site data analysis. The validity of the data is tested through the degree of trust, alienation, dependability and certainty. The findings of this study were: first, form (configuration) of islamic boarding school culture based on local wisdom is to integrate the salaf patterns which are adaptive to local culture and contain elements of modern which are termed of Moderate Traditionalists. Second, the style of islamic boarding school culture based on local wisdom is a mix figurative which is a mix of post figurative, co figurative, and pre figurative. Third, the typology of the development of islamic boarding school culture based on local skills is charismatic democratic.